Analisis Efektivitas Edukasi Perpajakan bagi Generasi Milenial melalui Media Sosial Instagram dalam Rangka Meningkatkan Kesadaran Wajib Pajak (Studi Kasus di Kantor Wilayah Direktorat Jenderal Pajak Jawa Barat II) - Fahrul Anwar Syadat; Raden Kusyeni; Erfa Fauziah (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
The Directorate General of taxes conducts various efforts to increase tax revenue by increasing taxpayer awareness through tax education activities to encourage taxpayers to carry out their obligations in accordance with applicable laws. The purpose of this study was to analyze the effectiveness of tax education. This study uses descriptive research with qualitative approach. Data collection from this study is by interview, observation and documentation. Instagram social media in order to increase taxpayer awareness is considered not effective, because there are still many people, especially millennials who do not know about the existence of tax education through Instagram Social Media Directorate General of taxes. From the study I got there are obstacles in the Regional Office of the Directorate General of taxation of West Java II is the lack of interest of the millennial generation related to taxation so indifferent to the information provided through social media instagram and the distribution of information that is less interesting. Efforts that can be made are active and thorough socialization to the entire community, especially the millennial generation, and making instagram content more interesting and easier to understand.